Prophetic preaching in a context of corruption in Nigeria : a practical theological investigation - Anthony, Ishaya (Stellenbosch : Stellenbosch University, 2017)
ENGLISH ABSTRACT: Globally, the quest to create corrupt free societies which promote human dignity and the quality of life is greatly envisioned and desired. While highly critical, most efforts in the fight against corruption, especially in Nigeria, tend to get hindered and absorbed in inaccessible policies. This intensifies violence, injustice and pauperisation. Nevertheless, using the ‘conflict paradigm’ within a socio-ecclesiological perspective, this study demonstrates that preaching, especially prophetic preaching, has the tenacity to foster appreciation and support for courageous collaboration and behavioral transformation of individauls and institutions that will strenghten the fight against corruption in Nigeria.Therefore, calls for prophetic pronouncement, prophetic exemplary life style, and prophetic imagination.